The Role of the Oral Microbiome in the Development and Treatment of Periodontal Disease: Functional Meta-Omics Evidence - Xiling Chen; Xiao Wu; Chunying He; Yijie Huang; Ruiqi Zhang; Qianqi Wu; Yiyan Chen; Jiajie Ouyang; Li Yan; Yingtao Lv; Yuan Su (Current Microbiology, 2026)

Corrigendum to “Irreversible male infertility from sleep restriction: A dual hit on testicular steroidogenesis and Keap1-Nrf2-mediated antioxidant defense” [Reprod. Toxicol. 138 (2025), 109083] - Keke Chen; Fengyou Luo; Xiling Huang; Kaixing Huang; Xiaoyu Liu; Qiping Hu; Changlong Xu (Reproductive Toxicology, 2026)

Dietary fiber-bound polyphenols in Canavalia gladiata seed coat: Optimization of conditions, identification and bioactivity assessment of acid, alkaline, and enzymatic extraction - Yue Qiu; Jiayan Xie; Jing Liang; Jianhua Xie; Yi Chen; Xiaobo Hu; Nan Sun; Xiling Wang; Qiang Yu (Food Chemistry, 2026)

Fertilization alters soil microbiome and root metabolites in grafted mulberry (Morus alba) with varied scion-rootstock combinations - Xin Chen; Haowen Fang; Yunfei Zhang; Zeyu Liu; Yingting Qin; Shuhang Cai; Jiayi Li; Lifu Zheng; Zhiwei Hou; Xiling Wang (Rhizosphere, 2025)

Irreversible male infertility from sleep restriction: A dual hit on testicular steroidogenesis and Keap1-Nrf2-mediated antioxidant defense - Keke Chen; Fengyou Luo; Xiling Huang; Kaixing Huang; Xiaoyu Liu; Qiping Hu; Changlong Xu (Reproductive Toxicology, 2025)

Characterization and decoding of volatile organic compounds in Moso bamboo shoots (Phyllostachys edulis L.) at different growth stages: A combined analysis by HS-GC-IMS, HS-SPME-GC‐MS, E-nose, and molecular docking - Lingzhi Zhang; Xiaozhen Peng; Xiling Wu; Xiaomei Tie; Jinrong Ma; Youjin Yi; Yulian Chen; Ke Li; Aixiang Hou; Jie Yang; Xingran Kou; Yu Xiao (Food Research International, 2025)

The wheat HSF transcription factor TaHSFC3B confers drought tolerance through ROS scavenging and ABA pathway in transgenic Arabidopsis and wheat (Triticum aestivum L.) - Yaning Bu; Tianqi Song; Jianfei Zhou; Xinpeng Lei; Xiling Chang; Siyi Li; Yuxin Wang; Xiaoxing Wang; Ling Kang; Dongsheng Chen; Jishan Xiang; Xiaoke Zhang (Planta, 2025)

Single-helix inclusion formation of V-type starch-lutein: Investigation of structural, physicochemical, and in vitro release - Jiajun Song; Xianxiang Chen; Xiling Wang; Qiang Yu; Yi Chen; Mingyue Shen; Xinyu lv; Huiliang Wen; Jianhua Xie (Food Bioscience, 2024)

Multi-omics analysis reveals anthocyanin synthesis is associated with drought stress tolerance in Chaenomeles speciosa flowers - Shuangyu Zhang; Xiling Chen; Yanshen Ren; Xingyue Xue; Yaping Xu; Qi Wang; Yanru Xie; Tengxun Zhang; Jiayi Lin; Xiaolu Chen; Houhua Li (Journal of Cleaner Production, 2024)

Removal of multiple pollutants in air pollution control devices of a coal-fired boiler installed with a flue gas condensation scrubber - Tailin Chen; Lejun Deng; Yuzhong Li; Jingwei Li; Xiling Zhao; Lin Fu (Journal of Cleaner Production, 2024)

Effects of leaf type, litter mass and rainfall characteristics on the interception storage capacity of leaf litter based on process simulation - Wenping Deng; Xiling Zheng; Shengsheng Xiao; Qi Chen; Yaoyao Gao; Ling Zhang; Jiahui Huang; Tianjun Bai; Songhua Xie; Yuanqiu Liu (Journal of Hydrology, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

RNA-seq for comparative transcript profiling in leaves of strawberry seedlings under salinity stress - Rui Zhang; Qiuli Du; Wenzhe Zhao; Long Yang; Dongmei Li; Xiude Chen; Wei Xiao; Xiling Fu; Chao Yang; Ling Li (Plant Biotechnology Reports, 2023)

Antibacterial effect of Cu2O/TiO2 photocatalytic composite on Pseudomonas marginalis pv. marginalis - Ying Jiang; Mengna Ding; Lang Liu; Jianguo Cao; Liuhong Chen; Guozheng Huang; Yuning Huo; Xiling Dai (Archives of Microbiology, 2022)

Adiantic acid, a new unsaturated fatty acid with a cyclopropane moiety from Adiantum flabellulatum L. - Junping Chen; Yichen Li; Jianguo Cao; Jinwen Huang; Can Jiang; Xiling Dai; Guozheng Huang (Natural Product Research, 2022)

Effectiveness of Disinfectants Suitable for Inactivating SARS-CoV-2 at Cold-Chain Temperature - Xiaosong Wu; Yin Chen; Ling Wang; Xiling Guo; Lunbiao Cui; Yiming Shen; Fang Li; Hong Sun; Liubo Zhang; Jin Shen; Yan Xu (Food and Environmental Virology, 2022)

Rapid and sensitive identification of pleural and peritoneal infections by droplet digital PCR - Fangmei Zhou; Shoudong Sun; Xiling Sun; Ye Chen; Xuejing Yang (Folia Microbiologica, 2021)

The mitochondrial genome of Mesocapnia daxingana (Plecoptera: Capniidae) - Ying Wang; Jinjun Cao; Weihai Li; Xiling Chen (Conservation Genetics Resources, 2017)

Reduction in Autophagy by (-)-Epigallocatechin-3-Gallate (EGCG): a Potential Mechanism of Prevention of Mitochondrial Dysfunction After Subarachnoid Hemorrhage - Ying Chen; Liyong Huang; Huiyong Zhang; Xiling Diao; Shuyang Zhao; Wenke Zhou (Molecular Neurobiology, 2017)

Genome-wide identification of WRKY family genes in peach and analysis of WRKY expression during bud dormancy - Min Chen; Qiuping Tan; Mingyue Sun; Dongmei Li; Xiling Fu; Xiude Chen; Wei Xiao; Ling Li; Dongsheng Gao (Molecular Genetics and Genomics, 2016)

Minimal physiologically-based pharmacokinetic (mPBPK) model for a monoclonal antibody against interleukin-6 in mice with collagen-induced arthritis - Xi Chen; Xiling Jiang; William J. Jusko; Honghui Zhou; Weirong Wang (Journal of Pharmacokinetics and Pharmacodynamics, 2016)

Erratum to: Elevated Expression of Acid-Sensing Ion Channel 3 Inhibits Epilepsy via Activation of Interneurons - Qingqing Cao; Wei Wang; Juan Gu; Guohui Jiang; Xiling Bian; Kewei Wang; Zucai Xu; Jie Li; Guojun Chen; Xuefeng Wang (Molecular Neurobiology, 2016)

Antioxidative and Cardioprotective Effects of Total Flavonoids Extracted from Dracocephalum moldavica L. Against Acute Ischemia/Reperfusion-Induced Myocardial Injury in Isolated Rat Heart - Jiangtao Jiang; Xuan Yuan; Ting Wang; Hongmei Chen; Hong Zhao; Xinyan Yan; Zhiping Wang; Xiling Sun; Qiusheng Zheng (Cardiovascular Toxicology, 2014)